2021
DOI: 10.1111/1759-7714.14274
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitor‐related adverse events in lung cancer: Real‐world incidence and management practices of 1905 patients in China

Abstract: Background: Immune checkpoint inhibitors (ICIs) are the standard treatment for advanced lung cancer, but immune-related adverse events (irAEs) remain poorly understood, especially in a real-world setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
3
18
1
Order By: Relevance
“…In a retrospective French cohort of 270 patients the outcomes were also better in patients with irAEs, showing an OS NR vs. 8.21 m, respectively (HR = 0.2); the PFS was 5.2 vs. 1.97 m (HR = 0.42); and ORR was 21.3 vs. 5.7% ( 27 ). Similar data has been observed in an Asian study about patients treated with ICIs in which DFS is higher in the subset of patients who developed toxicity ( 28 ). Other similar series have been published reporting similar outcomes ( 29 , 30 ).…”
Section: Association Between Iraes and Prognosis In Solid Tumorssupporting
confidence: 87%
“…In a retrospective French cohort of 270 patients the outcomes were also better in patients with irAEs, showing an OS NR vs. 8.21 m, respectively (HR = 0.2); the PFS was 5.2 vs. 1.97 m (HR = 0.42); and ORR was 21.3 vs. 5.7% ( 27 ). Similar data has been observed in an Asian study about patients treated with ICIs in which DFS is higher in the subset of patients who developed toxicity ( 28 ). Other similar series have been published reporting similar outcomes ( 29 , 30 ).…”
Section: Association Between Iraes and Prognosis In Solid Tumorssupporting
confidence: 87%
“…The correlation between irAEs and effective was not analyzed in our study due to confounding factors in the real world. However, based on the mechanism of action of ICIs, some published studies have shown that irAEs are associated with substantially improved ORR, DCR, PFS, and OS in patients who were treated with ICIs, and some experts consider irAEs to be a projection of the overall immune response to ICI therapy ( Kobayashi et al, 2020 ; Kotwal et al, 2020 ; Shi et al, 2022 ). A prospective study showed that the development of vitiligo during melanoma treatment increases the likelihood of a positive clinical efficacy ( Hua et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 studies [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] included 5404 patients on ICIs, and 101 developed CAEs for an incidence of 0.15–37.78% in which grade 3–5 CAEs accounted for 55.4%. Commonly encountered cardiotoxicities included arrhythmia (32.7%), cardiac-related chest pain (24.8%), elevated cTnI or myocarditis (23.8%), cardiomyopathy (20.8%), pericardial disease (11.9%), and acute coronary syndrome (10.9%).…”
Section: Cardiotoxicity In Different Types Of Cancermentioning
confidence: 99%